Анализ исторических аспектов развития гольфа, и перспективы его развития, в мировой спортивной практике - Павлюк, Ирина Сергеевна (My University, 2013)
На сегодняшний день, гольф является самым дорогим, престижным и респектабельным видом спорта. Гольф - это не просто игра, а оздоровление, закаливание и времяпровождение - это новые круги общения, умение реализовывать себя и свои идеи в жизнь, думать, анализировать и рассчитывать. History of development of golf is considered in the article. The features of his functioning and factors are analysed influencing on his development. The process of forming of the system of professional golf is grounded and the basic prospects of his development are certain. A complex analysis is conducted which allowed to set the dynamics of development of golf, and also to define external and internal factors substantially influencing on his development
Keywords: гольф; кафедра фізичного виховання; golf